2012
DOI: 10.1021/cm300301c
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic MFe2O4 (M = Fe, Co, Mn) Nanoparticles: Tuning the Particle Size and Magnetic Properties through a Novel One-Step Coprecipitation Route

Abstract: Superparamagnetic ferrite nanoparticles (MFe 2 O 4 , where M = Fe, Co, Mn) were synthesized through a novel one-step aqueous coprecipitation method based on the use of a new type of alkaline agent: the alkanolamines isopropanolamine and diisopropanolamine. The role played by the bases on the particles' size, chemical composition, and magnetic properties was investigated and compared directly with the effect of the traditional inorganic base NaOH. The novel MFe 2 O 4 nanomaterials exhibited high colloidal stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
256
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 478 publications
(288 citation statements)
references
References 67 publications
27
256
1
4
Order By: Relevance
“…This, however, is not unusual for nanomaterials and is often associated with surface spin canting and others size-related effects. [67][68][69] More importantly, the hysteresis curves confirm the magnetic easy axis as lying perpendicular to the film plane, as already indicated by the FC data. The "saturation" field is lower and the remanent magnetization and coercive fields are larger for the out-of-plane direction, which is particularly evident in the measurements at room temperature (the in-plane loop is significantly more skewed).…”
Section: Resultssupporting
confidence: 79%
“…This, however, is not unusual for nanomaterials and is often associated with surface spin canting and others size-related effects. [67][68][69] More importantly, the hysteresis curves confirm the magnetic easy axis as lying perpendicular to the film plane, as already indicated by the FC data. The "saturation" field is lower and the remanent magnetization and coercive fields are larger for the out-of-plane direction, which is particularly evident in the measurements at room temperature (the in-plane loop is significantly more skewed).…”
Section: Resultssupporting
confidence: 79%
“…As seen in Table 4 the maghemite sample has a higher saturation magnetization (37.50 emu/g) compared to that of magnetite (32.87 emu/g), opposite to expectation. This is attributed to the presence of nonstoichiometry and a thicker "dead layer" in the magnetite particles compared to those of maghemite [43]. Nonstoichiometry implies partial oxidation of magnetite to maghemite, as already observed in the Mössbauer spectra.…”
Section: Vsm Magnetometrymentioning
confidence: 56%
“…This matches with the findings of Pereira et al [42] who found that saturation magnetization tends to decrease with decreasing particle size. Furthermore, there is something called digestion time which refers to the time one waits after the reaction temperature is reached before adding Oleic acid to the solution [37].…”
Section: Synthesis Proceduressupporting
confidence: 93%
“…Furthermore, there is something called digestion time which refers to the time one waits after the reaction temperature is reached before adding Oleic acid to the solution [37]. Ayyapan et al [37] found that average particle size increased from 14 nm to 19 nm as the digestion time was increased from 1 min to 120 min whereas the saturation magnetization decreased (which again corresponds to the findings of Pereira et al [42] that decreasing particle size leads to decreasing saturation magnetization).…”
Section: Synthesis Proceduresmentioning
confidence: 60%